Electroretinogram evaluation of equine eyes with extensive 'bullet‐hole' fundic lesions. (30th April 2014) - Allbaugh, Rachel A.; Ben‐Shlomo, Gil; Whitley, R. David
Abstract: Objective: To evaluate the impact of extensive bullet‐hole nontapetal fundic lesions in horses on retinal function as measured by full‐field electroretinography (ERG). Materials and Methods: Full‐field ERG was performed on two horses with numerous bullet‐hole lesions in the nontapetal fundus of both eyes. The ERG was first recorded from the eye with the more extensive lesions in response to a low‐intensity light stimulus (0.03 cd s/m 2 ) that was given at times ( T ) T  =   5, 10, 15, 20 min of dark adaptation. Consecutively, combined rod–cone response was evaluated bilaterally in response to high‐intensity light stimulus (3 cd s/m 2 ), followed by cone function evaluation by flicker stimulus (3 cd s/m 2 at 30 Hz). Off‐line analysis of the ERG recordings was then performed. Results: Despite extensive bullet‐hole lesions in the nontapetal fundus bilaterally in both horses, retinal function as measured by ERG did not show any observable deficits. The b‐wave amplitude of the full‐field ERG increased continuously from 5 to 20 min of dark adaptation peaking at 446 μv and 377 μv for horse number 1 and 2, respectively. The b‐wave amplitudes of the combined rod–cone response were OS‐ 459 μv and OD‐ 392 μv for horse number 1 and OS‐ 491 μv and OD‐ 608 μv for horse number 2. The amplitude of the flicker ERG for horse number 1 was OS‐ 86 μv and OD‐ 110 μv and for horse number 2, OS‐ 80 μv and OD‐ 74 μv. Conclusions: Extensive bullet‐hole chorioretinal lesions do not appear to compromise outer retinal function in these horses.